+0  
 
0
353
1
avatar

18/x^2-3x - 6/x-3 = 5/x

Guest May 14, 2017
 #1
avatar+87564 
+1

I think we have

 

18 / (x^2-3x) -  6/(x-3) = 5/x    

 

18 / [ x (x - 3) ]  -  6 / (x - 3)   =  5/ x           the LCD  is  x(x-3)

 

Multiplying through by the LCD produces

 

18  - 6x  = 5 (  x - 3)

 

18 - 6x  = 5x - 15      add 6x, 15 to both sides

 

33 =  11x          divide both sides by 11

 

3 = x        thus.......there is no solution since this value for x makes an original denominator  = 0

 

 

cool cool cool

CPhill  May 15, 2017

11 Online Users

avatar
avatar
avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.